Modified Zexie decoction improves phlegm-dampness type stage I hypertension by regulating the gut-immune-kidney axis - Hu, Zeqi; Jia, Jiujie; Su, Yiyan; Gu, Yihao; Cheng, Bingbing; Jiang, Ninghua (Frontiers in Pharmacology, 2025)
IndroductionHypertension pathogenesis increasingly implicates gut microbiota‐host crosstalk, where immune regulation bridges gut dysbiosis and renal dysfunction. Phlegm-dampness hypertension—a prevalent Traditional Chinese Medicine (TCM) syndrome typified by metabolic, immune, and renal anomalies—demands novel interventions. Modified Zexie Decoction (MZXD), a TCM formula with documented antihypertensive and anti-inflammatory properties, may target the gut‐immune‐kidney axis. This study investigated MZXD’s efficacy in Stage I phlegm-dampness hypertension via this axis.MethodsThirty Stage I phlegm‐dampness hypertension patients received MZXD for 42 days. Pre‐ and post‐treatment measurements included blood pressure, serum immune markers, renal function parameters, gut microbiota, and short‐chain fatty acids (SCFAs).ResultsMZXD significantly reduced systolic/diastolic blood pressure (P < 0.05). Gut microbiota diversity increased, shifting toward healthy profiles. SCFA levels rose markedly (P < 0.01). Immune markers (P < 0.05) and renal function improved (P < 0.05).DiscussionMZXD alleviates phlegm‐dampness hypertension by modulating the gut-immune‐kidney axis: enhancing microbial diversity, boosting SCFAs, attenuating inflammation, and improving renal function. This first systematic validation positions MZXD as a promising multi-target therapy. Future studies should explore clinical scalability and mechanistic depth.